Metamorphosen des Leids: Die Nicht-Thematisierung sexueller Gewalt gegen Kinder in der antiken Historiographie - Mauritsch , Peter (Österreichische Zeitschrift für Geschichtswissenschaften, 2017)
Abstract: Metamorphoses of Suffering. The Non-Thematisation of Sexual Violence Against Children in Ancient Historiography. Children are seldom mentioned in ancient literature, and in contrast to modern efforts to protect children as well as possible, no corresponding idea was conceptualized in Greek and Roman antiquity. Even as girls and boys oen were victims of violence – especially in wartime but also in the hand of adults, with or without sexual abuse – their suffering never was understood as an aggression against them as individuals but only was used by historians and biographers as a means to depict the evil character of statesmen, generals or emperors. &e paper deals with the con'nements ancient historiography had to heed when describing acts of (sexual) violence.